Revenue effects of tax rate changes in Alberta - Ferede, Ergete (My University, 2025)
Alberta has in the past prided itself as having an overall tax advantage relative to the rest of Canada. As recently as 2014, the province offered a highly competitive tax environment. Not only was it the only province in Canada without a provincial retail sales tax, it also levied a single personal income tax (PIT) rate of 10%, the lowest in the country. Additionally, Alberta boasted the lowest corporate income tax rate. The province’s tax policy changed in 2015, when the newly elected NDP provincial government raised the corporate income tax rate (CIT) from 10% to 12%, and replaced the single PIT rate with a five-bracket system. As a result of this policy change, Alberta’s provincial top marginal PIT rate jumped from 10% to 15% in 2015, eroding the province’s tax advantage. Alberta now has the tenth highest top marginal personal income tax rate in North America, and its tax competitiveness ranking, particularly when compared with similar energy-based North American jurisdictions, is lower.
Keywords: Alberta; revenue effects; tax rate changes; personal income tax (PIT); corporate income tax (CIT)